2020
DOI: 10.1111/1467-9566.13120
|View full text |Cite
|
Sign up to set email alerts
|

How does cultural capital keep you thin? Exploring unique aspects of cultural class that link social advantage to lower body mass index

Abstract: A widely used indicator for cultural class is strongly related to a lower body mass index (BMI): cultural capital measured as 'highbrow' taste. This study's objective was to theorise and measure aspects of cultural class that are more plausibly linked to low BMI, and subsequently explore their relevance. Building on Bourdieusian theory we derive four of those aspects: 'refinement' (valuing form and appearance over function and substance), 'asceticism' (self-imposed constraints), 'diversity' (appreciation of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
1
9
0
2
Order By: Relevance
“…Our findings that low food-related cultural capital was associated with low fruit and vegetable consumption and overall diet quality was consistent with previous literature. ( 7, 10, 12 ) As anticipated, total incorporated cultural capital is a stronger predictor for diet compared to objectivised cultural capital. This potentially relates to the method of calculation for these two variables where the total incorporated cultural capital included a much wider scope of factors compared to objectivised cultural capital.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our findings that low food-related cultural capital was associated with low fruit and vegetable consumption and overall diet quality was consistent with previous literature. ( 7, 10, 12 ) As anticipated, total incorporated cultural capital is a stronger predictor for diet compared to objectivised cultural capital. This potentially relates to the method of calculation for these two variables where the total incorporated cultural capital included a much wider scope of factors compared to objectivised cultural capital.…”
Section: Discussionsupporting
confidence: 63%
“…(7) With this in mind, more recent studies have linked cultural resources to diet and health inequalities, and have identified cultural capital, constructed by culture-based activities, knowledge and perceptions, as a good predictor for diet quality. (7)(8)(9)(10)(11)(12)(13) For example, a Dutch study reported that low cultural capital was strongly correlated with poor diet outcomes (7) while a study in Norway reported cultural capital as a good predictor for healthy eating patterns amongst adolescents. (8) Culture is a resource acquired through social learning that is critical to people's behaviour, norms, values and knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…As another consequence of this socialization, their lifestyles differ from those of many less‐educated individuals in terms of, e.g. cultural consumption (Katz‐Gerro, 2002 ; Van Eijck, 1999 ) and political viewpoints (Noordzij et al, 2019 ; Spruyt et al, 2016 ), as well as health (Oude Groeniger et al, 2020 ; Pampel et al, 2010 ) and food practices (Oude Groeniger et al, 2017 ; Pampel, 2012 ). In and of themselves, these lifestyle differences are no cause for anti‐institutionalist tendencies by less‐educated individuals.…”
Section: A Novel Explanation For Less‐educated Individuals’ Limited N...mentioning
confidence: 99%
“…Finally, e mbodied cultural capital refers to various kinds of behaviours, skills and socially relevant, valued knowledge acquired through formal and informal education in schools, families, sport clubs, etc. ( Abel, 2007 , 2008b ; Oude Groeniger et al, 2020 ). It comprises health-relevant tastes, preferences and dispositions that are physically embodied, part of the habitus and practised through lifestyles ( Cockerham, 2005 ).…”
Section: Critical Health Literacy and The Reproduction Of Inequality—...mentioning
confidence: 99%